Creatine-kinase concentration of the cerebrospinal fluid in childhood acute bacterial meningitis - Fx. Wikan Indrarto, Fx. Wikan Indrarto (Universitas Gadjah Mada, 1999)
Background: Acute bacterial meningitis is one of paediatric emergency cases which results in high morbidity and mortality. Diagnostic procedures using cerebrospinal fluid (CSF) are often unsatisfactory. A simple and rapid procedure is required for early diagnosis and prompt treatment.Objectives: The aims of this study were to assess total cerebrospinal fluid creatine-kinase (CSF-CK) level in childhood acute bacterial meningitis and to assess the diagnostic values of CSF-CK level compare with routine CSF analysis (i.e. cell count, morphology, chemical, C reactive protein and culture) which is accepted as diagnostic gold standard for acute meningitis.Materials and methods: All patients hospitalized in the Pediatric Department Sardjito Hospital for suspected acute bacterial meningitis in July-December 1998, underwent lumbar puncture. The level of CSF-CK and routine analyses were examined for diagnosis acute bacterial meningitis.Results: Forty five children with suspected meningitis were included in this study. CSF-CK 16 U/I had sensitivity 50%, specificity 80%, positive predictive value 42%, negative predictive value 85% and likelihood ratio 2,75. Mean of CSF-CK in childhood acute bacterial meningitis was 82,84 U/I.Conclusion : CSF-CK level was not sensitive, but it is a specific diagnostic test for childhood bacterial meningitis.Key words: acute bacterial meningitis - CK-CSF - diagnostic test